Chebyshev Collocation Method for Solving Caputo Fractional Interface Problem (Journal of Informatics and Mathematical Sciences, 2025)
In this study a collocation strategy for the solution of the fractional interface problem is proposed. The spatial derivatives are computed using interpolation with Chebyshev functions. We elaborate the analysis that leads to an a priori error estimation. Different numerical examples are presented to show the applicability and effectiveness of the developed approach.